Pengaruh Pemberian Vanadil Sulfat dan Kromium (III) Klorida terhadap Fungsi Ginjal Mencit Putih Diabetes - Dwisari Dillasamola; Surya Dharma; Helmi Arifin (Jurnal Sains Farmasi & Klinis, 2014)
The objective of this study was to identify the effect of two heavy metals, vanadyl sulphate and chromium (III) chloride on creatinine level of hyperglycemic mice induced by dexamethasone 11mg/kg. The experimental animals were grouped into five groups comprised of 5 white mice. Group I was used as control group, only received standard feeding and food supplement. Group II-V were induced with dexamethasone 11mg/kg to increase the blood glucose level. Group III was also given chromium (III) chloride 5.2 ug/20g. Group IV was also given vanadyl sulphate at the dose of 0.78 mg/20g. Group V received combination of vanadyl sulphate 0.39 mg/20g and chromium (III) chloride 2.6 ug/20g. The level of blood creatininewas determined by enzymatic method conducted for 42 days and observations were taken at day 7, 21 and 42. This study concluded that administration of vanadyl sulphate and chromium (III) chloride combination significantly reduced blood creatinine level of white mice (p<0,05).